Reasons and recognition essays on the philosophy of T.M. Scanlon - Wallace, R. Jay.; Kumar, Rahul, 1967-; Freeman, Samuel Richard (New York : Oxford University Press, 2011)
This work brings together 14 papers on an array of topics from the many areas to which philosopher Thomas Scanlon has made path-breaking contributions, each of which develops a distinctive and independent position while critically engaging with central themes from Scanlon's own work in the area.
Description based on print version record.
Includes index.
Keywords: Scanlon, Thomas; Philosophy, American -- 20th century